PENGEMBANGAN MEDIA PEMBELAJARAN KIMIA BERBASIS POWTOON PADA POKOK BAHASAN HIDROKARBON DI KELAS XI SMA/SEDERAJAT - Liani '; Rini '; R. Usman Rery (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract This study is aimed to develop learning media by using PowToon on the subject of Hydrocarbon at SMA/MA. The result of this study is a product of learning media in the form of CD (compact disk) for Hydrocarbon subject which has contents as follows: the characteristic of carbon, alcana,alchene and alcuna, the application carbon in daily. This study used Research and Development (R&D) method with ADDIE model which has five stages of development; they are analysis, design, development, implementation, and evaluation. The development model was modified by the writer only until the development stage. The result of validation test showed that learning media on the subject of Hydrocarbon is valid with the result of validation by media experts and material experts 89,63%, so the developed learning media is properly used on the learning and teaching process. The result of the development has been limited test on 22 students and then 2 chemistry teacher in senior high school average score percentase obtained by 89,63%Key Words : Development of learning media, PowToon, Hydrocarbon